2016
DOI: 10.7251/afts.2016.0815.041h
|View full text |Cite
|
Sign up to set email alerts
|

Application of Earth and Straw Mixtures in Modern Building

Abstract: SUMMARY:Building with earth is widespread and still mostly based on traditional experiences. Increasing demands in energy consumption reduction during the construction and exploitation of buildings put more and more in the focus the good features of houses built with earth.Testing of earth mixtures with other natural materials showed that it can get even a quality of bricks, which indicates the lack of appropriate standards for this type of construction.Testing are performed with mixes of earth and straw inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Our earlier studies already showed that light-clay materials can have good mechanical characteristic [10,12].The calculation of the average energy consumption for heating per annum for the average design temperature is given in the Table 7. Comparative analysis showed the variation in features between the rammed earth walls and sandwich wall with several layers of materials including a layer with enhanced thermal insulation characteristics.…”
Section: Calculation For Rammed Earth Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our earlier studies already showed that light-clay materials can have good mechanical characteristic [10,12].The calculation of the average energy consumption for heating per annum for the average design temperature is given in the Table 7. Comparative analysis showed the variation in features between the rammed earth walls and sandwich wall with several layers of materials including a layer with enhanced thermal insulation characteristics.…”
Section: Calculation For Rammed Earth Constructionmentioning
confidence: 99%
“…The wetting of the exposed walls by atmospheric precipitation should only be avoided during construction (until the roof, eaves, insulation plinths, etc. are finished), although recent studies showed that slight increase in moisture content of dry rammed-earth walls will not affect the compressive strength significantly [9,10,11,12,13].…”
Section: Construction Of Rammed Earth Walls For Buildingsmentioning
confidence: 99%
See 1 more Smart Citation